Triple therapy in the management of chronic obstructive pulmonary disease: systematic review and meta-analysis. (6th November 2018) - Zheng, Yayuan; Zhu, Jianhong; Liu, Yuyu; Lai, Weiguang; Lin, Chunyu; Qiu, Kaifen; Wu, Junyan; Yao, Weimin
Abstract: Objective: To compare the rate of moderate to severe exacerbations between triple therapy and dual therapy or monotherapy in patients with chronic obstructive pulmonary disease (COPD). Design: Systematic review and meta-analysis of randomised controlled trials. Data sources: PubMed, Embase, Cochrane databases, and clinical trial registries searched from inception to April 2018. Eligibility criteria: Randomised controlled trials comparing triple therapy with dual therapy or monotherapy in patients with COPD were eligible. Efficacy and safety outcomes of interest were also available. Data extraction and synthesis: Data were collected independently. Meta-analyses were conducted to calculate rate ratios, hazard ratios, risk ratios, and mean differences with 95% confidence intervals. Quality of evidence was summarised in accordance with GRADE methodology (grading of recommendations assessment, development, and evaluation). Results: 21 trials (19 publications) were included. Triple therapy consisted of a long acting muscarinic antagonist (LAMA), long acting β agonist (LABA), and inhaled corticosteroid (ICS). Triple therapy was associated with a significantly reduced rate of moderate or severe exacerbations compared with LAMA monotherapy (rate ratio 0.71, 95% confidence interval 0.60 to 0.85), LAMA and LABA (0.78, 0.70 to 0.88), and ICS and LABA (0.77, 0.66 to 0.91). Trough forced expiratory volume in 1 second (FEV1) and quality of life were favourable with triple therapy. The overall safety profile of triple therapy is reassuring, but pneumonia was significantly higher with triple therapy than with dual therapy of LAMA and LABA (relative risk 1.53, 95% confidence interval 1.25 to 1.87). Conclusions: Use of triple therapy resulted in a lower rate of moderate or severe exacerbations of COPD, better lung function, and better health related quality of life than dual therapy or monotherapy in patients with advanced COPD. Study registration: Prospero CRD42018077033.